PKM Literasi Pemasaran Digital Berbasis Green Economy Pada Kelompok Wanita Tani Perkotaan di Kota Makassar - Sitti Hajerah Hasyim; Muhammad Hasan; Citra Ayni Kamaruddin; Nur Arisah; Hikmayani Subur (MALLOMO: Journal of Community Service, 2024)
Marketing of the agricultural products of the Lorong Anggrek Farming Women's Group, Bara-baraya Village is still limited to word of mouth, from house to house, especially within the Bara-baraya Subdistrict, even though these agricultural products have the potential to be marketed online, especially since the Lorong Anggrek Women's Farming Group is in the city center. Makassar. Therefore, the aim of this service is that digital marketing assistance for Green Economy-based products is carried out by creating special accounts for product promotions and orders, namely WhatsApp, Instagram, Facebook, TikTok accounts and Shopee accounts. Next, creative content is created in the form of flyers and videos which are posted on YouTube and social media as well as through the TikTok application. The method applied is providing assistance and training to members of the Lorong Anggrek Women's Farming Group regarding packaging, labeling and marketing through online media to increase sales of agricultural products to increase the added value of production in the Lorong Anggrek Women's Farming Group, Bara-baraya Village.